Prognosis in HR-positive metastatic breast cancer with HER2-low versus HER2-zero treated with CDK4/6 inhibitor and endocrine therapy: a meta-analysis - Xia, Lin-Yu; Cao, Xu-Chen; Hu, Qing-Lin; Xu, Wei-Yun (Frontiers in Oncology, 2024)
The combination of CDK4/6 inhibitors (CDK4/6i) and endocrine therapy (ET) is currently the standard first-line treatment for patients with metastatic hormone receptor positive (HR+), and HER2-negative (HER2-) breast cancer. However, the impact of HER2 status on the prognosis of patients receiving CDK4/6i and ET remains unclear. The meta-analysis was conducted to evaluate different outcomes between HER2-low and HER2-zero patients in advanced HR+ breast cancer receiving CDK4/6i and ET. Methods: A systematic search was performed in PubMed and EMBASE databases for relevant published literature. Objective response rate (ORR), overall survival (OS), and progression-free survival (PFS) were pooled by fixed or random effects models. Results: Overall, 12 studies with 3567 patients were eligible for analysis. The pooled analysis suggested that no significant differences were observed in terms of ORR and OS between HER2-low and HER2-zero patients who underwent CDK4/6i and ET. Similarly, no significant difference in PFS was found between HER2-low and HER2-zero patients who underwent post-line CDK4/6i and ET or first-line Palbociclib and ET.However, in patients who received mixed-line ( not a single treatment line) or first-line CDK4/6i and ET, the PFS was significantly shorter in the HER2-low subgroup than in the HER2-zero subgroup